A RARE CASE OF ALVEOLAR SARCOMA OF THE PARAPHARYNGEAL SPACE - E. N. Novozhilova; A. P. Fedotov; V. N. Grinevich; V. I. Kozlov; I. V. Kuzmin (Опухоли головы и шеи)
The paper describes the rare malignancy alveolar soft tissue sarcoma. The tumor was located in the parapharyngeal space; it was detected during pregnancy. The authors give the data available in the literature on the clinical manifestations of this disease, the specific features of morphological diagnosis, and treatment policy. The described case focuses on the complexities of diagnosis and preoperative preparation and surgical techniques.